Análisis de la relación Costo-Volumen-Utilidad y su impacto en la rentabilidad del restaurante “La Boutique del Sabor”, cantón Chimbo, provincia Bolívar, periodo 2022. - Salinas Gavi, Gisell Mercedes (2024)
The purpose of this study was to analyze the Cost-Volume-Utility relationship and its impact on the profitability of the restaurant "La Boutique del sabor" in Chimbo Canton, Bolivar Province, during the period 2022. A methodology that included applied, descriptive and field research was applied, as well as a mixed approach that combined quantitative and qualitative methods. A variety of data collection techniques and instruments, such as interviews and surveys, were used to obtain detailed information about the restaurant and its financial performance. The results revealed that the restaurant has a positive profitability and that specific dishes or products contribute significantly to its profitability. The importance of implementing an inventory control system to prevent economic losses due to product obsolescence and to optimize the use of resources was highlighted. Based on these findings, several recommendations were made, such as finding ways to reduce costs without compromising service quality, incorporating new profitable dishes, designing targeted marketing strategies, and providing staff training.